Simulation program. Type I error and power. Violation of normality and sphericity in one-way repeated measures ANOVA. - Blanca-Mena, María José; Alarcón-Postigo, Rafael; Arnau, Jaume; García-Castro, F. Javier; Bono Cabré, Roser (Universidad de Málaga, 2025)
The archive contains the SAS code to analyze the performance of the F-statistic, and Greenhouse-Geisser (F-GG) and Huynh-Feldt (F-HF) F adjustments in terms of Type I error and power with non-normal data under violation of sphericity.
Keywords: Análisis de varianza; Psicometría; Sphericity; Greenhouse-Geisser adjustment; Huynh-Feldt adjustmen; F-statistic; Normality; Type I error